Analysis of changes in anthropometric parameters of dentition and tongue mobility during orthodontic treatment - Melnyk, Alona (The Ukrainian Scientific Medical Youth Journal, 2026)
diagnosing the topography and severity of morphological disorders, establishing a final diagnosis, justifying the optimal plan and timing of orthodontic treatment, and assessing the degree of changes achieved in each clinical variant is made possible by analyzing changes in anthropometric indicators of the dentition, which is an integral part of a personalized approach and can only be carried out if orthodontic appliances are correctly selected. Aim of the study: to analyze changes in anthropometric indicators of the dentition of the upper and lower jaws and tongue mobility during orthodontic treatment of children with distal occlusion complicated by anatomical and functional disorders of the tongue, depending on the type of orthodontic appliances used. Materials and methods. We analyzed anthropometric indicators of the dentition of the upper and lower jaws and tongue mobility before and during orthodontic treatment of children aged 5 to 12 years with distal occlusion complicated by anatomical and functional disorders of the tongue (n=31). Results and their discussion. For the upper jaw, it was found that the type of orthodontic appliances used is primarily associated with different severity of transverse changes in the frontal region. For the interdental width of the dentition, statistically significant differences were found between the groups: the largest average increase was when using Marco Rosa appliances (4.5±1.1 mm), somewhat less - Mew appliances (4.1±0.6 mm) and the smallest - Schwarz, Flis P.S.-Filonenko V.V. and Twin Block appliances (3.0±0.4 mm), which may indicate a slightly different potential of their action in expanding the upper dentition of the specified segment. For the lower jaw, a tendency towards more pronounced transverse expansion was observed when using Flis P.S.-Filonenko V.V. and Twin Block appliances. The average interdental width was 2.4±1.0 mm versus 1.9±0.9 mm when using Schwarz appliances. Patients with the I degree of mobility, when establishing violations of the phonetic side of speech, were provided with standard corrective speech therapy, with the II degree - speech therapy correction, which consisted of a preparatory stage, which consisted in the formation of kinetic and kinestatic praxis by selecting individual myogymnastics and a stage of sound production, which included the formation of articulatory structures of impaired groups of sounds. Children with the III degree of mobility showed a low level of performance of all tests. Their speech disorders were associated with congenital or acquired defects in the anatomical structure of the organs of the peripheral articulatory apparatus. In addition to orofacial myofunctional gymnastics, additional speech technologies were used. Functional tests after speech therapy correction and the simultaneous use of orthodontic appliances, especially the lower jaw, determined the positive dynamics of tongue mobility. Conclusions. Scientific evidence of the effectiveness of orthodontic treatment is based on the criteria for changes in anthropometric indicators of the dentition and comparison of the results of functional tests. In the case of the tongue in a lower position and reduced mobility, orthodontic treatment of children with distal occlusion, complicated by anatomical and functional disorders of the tongue, is most effectively carried out with the use of maxillary orthodontic appliances without an expanded base in the anterior 1/3; the base of the mandibular appliances plays the role of a sublingual mouthpiece, which, in addition to the directed effect of jaw expansion at the dental and alveolar levels, contributes to the normalization of the physiological position of the organ.